2018
DOI: 10.1139/cjas-2017-0121
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inflammation on the synthesis of luteinizing hormone and gonadotropin-releasing hormone receptor expression in thepars tuberalisof ewe during different photoperiodic conditions

Abstract: The study was designed to determine the effect of endotoxin-induced inflammation on luteinizing hormone (LH) synthesis and gonadotropin-releasing hormone (GnRH) receptor expression in the pars tuberalis (PT) of ewes during anestrous season and follicular phase taking into account the time of the day. Moreover, the effect of inflammation on the release of melatonin and its type I receptor gene expression in the PT was also determined. Lipopolysaccharide administration reduced nocturnal release of melatonin only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…The amount of GnRHR determining the ability and storage strength of the pituitary gonadotropes in response to GnRH [ 48 ]. It was previously found that during inflammation the pituitary sensitivity to GnRH stimulation [ 9 ] and the expression of GnRHR in ewes were suppressed [ 49 , 50 ]. It is believed that the lower GnRHR gene expression in the pituitary during an immune/inflammatory challenge is mainly due to the lower secretion of the hypothalamic GnRH [ 1 , 45 , 46 , 47 ], which is one of the most important regulator of its own receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of GnRHR determining the ability and storage strength of the pituitary gonadotropes in response to GnRH [ 48 ]. It was previously found that during inflammation the pituitary sensitivity to GnRH stimulation [ 9 ] and the expression of GnRHR in ewes were suppressed [ 49 , 50 ]. It is believed that the lower GnRHR gene expression in the pituitary during an immune/inflammatory challenge is mainly due to the lower secretion of the hypothalamic GnRH [ 1 , 45 , 46 , 47 ], which is one of the most important regulator of its own receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time RT-PCR analysis was carried out with the use of the HOT FIREPol EvaGreen qPCR Mix Plus (Solis BioDyne, Tartu, Estonia) and HPLC-grade oligonucleotide primers (Genomed, Warszawa, Poland) in line with the method described elsewhere [ 34 ]. Specific primers to determine the expression of the genes of interest and housekeeping genes were chosen on the basis of our previous experience (see Table 2 ).…”
Section: Methodsmentioning
confidence: 99%